Drop jump force-time characteristics within NCAA Division I sprinters - Norwood, S.; Johnson, Q. R.; Nguyen, M.; Yang, Y.; Cabarkapa, D.; Fry, A. C. (International Journal of Exercise Science Conference Proceedings, 2025)
Generating force and being technically proficient are key components when sprinting maximally. For short distances like 60-meter, 100-meter, and 200-meter races, more information which examines lower-body muscular power within collegiate track and field populations is needed. PURPOSE: The purpose of this study was to analyze specific drop jump (DJ) force-time characteristics of collegiate sprinters. METHODS: 10 (male; n=5 [1 Olympian], height; 1.78-1.82m, weight; 67.5-79.8kg, and female; n=5, height; 1.6-1.73m, weight; 57.2-66.8kg) NCAA Division-I sprinters participated in this study. Average braking forces (ABF), average propulsive forces (APF), net impulse ratio (NIR) and DJ height were collected by using a uniaxial dual force plate system sampling at 1,000 Hz. Athletes performed three trials separated by 20-seconds from a 12-inch plyometric box with hands remaining on hips then rapidly redirecting to a maximal jump. Athletes were grouped by sex to compare performance. Descriptive statistics, Spearman`s rank correlation coefficient, and independent samples t-tests were calculated to analyze differences between groups. RESULTS: Significant strong positive correlations were observed between ABF (r = 0.792; p < 0.001), APF (r = 0.883; p < 0.001), NIR (r = 0.998; p < 0.001) and DJ height. Significant differences were observed between sexes for measures of ABF (p = 0.046) and APF (p = 0.002). However, no significant differences were observed for measures of DJ height or NIR. CONCLUSIONS: To conclude, the primary purpose of this investigation was to analyze specific drop jump (DJ) force-time characteristics of collegiate sprinters. Significant relationships between dynamic eccentric and concentric force production, transference capabilities, and DJ height were observed irrespective of sex. Additionally, no significant differences between sexes were observed for measures of jump height or NIR. Based on the findings of the current study, NCAA Division-I sprinters possess optimal force production and transference capabilities irrespective of sex. Therefore, dynamic exercises that emphasize the development and transference of absolute forces should be implemented within this population as they are strongly related to DJ ability, which may positively contribute to sprinting ability.